2011
DOI: 10.5539/ijef.v3n2p150
|View full text |Cite
|
Sign up to set email alerts
|

Causal Links Between Foreign Direct Investment and Trade in Turkey

Abstract: This paper investigates the empirical evidence on the link between foreign direct investment and trade (export and import) in Turkey over the period from 1992:01 to 2008:04 by using the minimum LM unit root test for stationarity; Granger and Dolado-Lüthkepohl tests for causality. The test results based on the bi-variate VAR model indicate that there is no evidence of causality between foreign direct investment and trade in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
3
0
3
Order By: Relevance
“…A 1% increase of direct investment by China into the CIS may accelerate energy export volumes by nearly 0.53%. This result corroborates the work of Santiago (1987), Dritsaki and Stiakakis (2014), and Sunde (2017), who discovered a positive relationship between FDI and trade flows, but it contradicts the work ofKiran (2011) who asserted that there exists no evidence of causality between FDI and trade.ⅴ. Among all of my regressors, the sign of the coefficient for PR is most interesting.…”
supporting
confidence: 86%
“…A 1% increase of direct investment by China into the CIS may accelerate energy export volumes by nearly 0.53%. This result corroborates the work of Santiago (1987), Dritsaki and Stiakakis (2014), and Sunde (2017), who discovered a positive relationship between FDI and trade flows, but it contradicts the work ofKiran (2011) who asserted that there exists no evidence of causality between FDI and trade.ⅴ. Among all of my regressors, the sign of the coefficient for PR is most interesting.…”
supporting
confidence: 86%
“…Regarding the effect of FDI on exports, the evidence is also mixed. While some found that increased levels of FDI positively affect exports (e.g., Lin, 1995;Zhang & Song, 2000;Liu et al, 2001;Dritsaki et al, 2004;Kutan & Vuksic, 2007;Xuan & Xing, 2008;Bhatt, 2013), others reported evidence that FDI has insignificant or even negative effect on exports (e.g., Hsiao & Hsiao, 2006;Jayachandran & Seilan, 2010;Kiran, 2011;Dritsaki & Stiakakis, 2014). There is evidence that FDI inflows improve trade balance (Anwar & Nguyen, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was suggested that expansion of FDI is beneficial for export promotion in selected countries. Kiran (2010) scrutinized the causal relationship between FDI and trade in Turkey by using quarterly data from 1992 to 2008. Results suggested no causal relationship between FDI and trade.…”
Section: Empirical Evidencementioning
confidence: 99%